Re-conceptualizing music education in the older adult life course : A qualitative meta-synthesis - Laes, Tuulikki; Creech, Andrea (Whioce Publishing, 2023)
The Seoul Agenda by UNESCO has set goals to develop arts education, ensuring that learners from all social backgrounds have lifelong access to arts education in a wide range of community and institutional settings. However, the purpose of lifelong learning for individuals beyond labor-market age has been largely overlooked, making it challenging to convince institutions, funders, and policymakers of its worth. The value accorded to the complex forms of lifelong learning in later life and the widely recognized health impacts of music on aging body and brain are the principal considerations to take into account when studying the effects of music education on older adults. In this study, we address the state-of-the-art research concerning older adults and music education in studies published in major peer-reviewed music education journals since the Seoul Agenda by UNESCO. We present the findings from a systematic literature review, followed by a qualitative meta-synthesis, focusing on the values, beliefs, and key concepts conveyed in the included studies. The findings of this study indicate that older adults are often portrayed narrowly and stereotypically, corroborating the issues in the sociology of aging. Our study highlights insights into the conceptualizations of music learning and participation in later life course and what these might mean for the policy and practice of later-life music education and the educational opportunities for older adults more broadly.
Keywords: musiikkikasvatus; ikääntyneet; ikääntyminen; elinikäinen oppiminen; musiikki; hyvinvointi; aikuiskoulutus